Feeding the gut microbiome: impact on multiple sclerosis - Bronzini, Matteo; Maglione, Alessandro; Rosso, Rachele; Matta, Manuela; Masuzzo, Federica; Rolla, Simona; Clerico, Marinella (Frontiers in Immunology, 2023)
Multiple sclerosis (MS) is a multifactorial neurological disease characterized by a chronic inflammation and immune-driven demyelination of central nervous system (CNS). The rising number of MS cases in the last decades could be partially attributed to environmental changes, among which the alteration of gut microbiome driven by novel dietary habits is now of particular interest. The intent of this review is to describe how diet could impact the development and course of MS by feeding gut microbiome. We discussed the role of nutrition and gut microbiota in MS disease, describing preclinical studies in the experimental autoimmune encephalomyelitis (EAE), and clinical studies of dietary intervention in MS, with a particular attention to gut metabolites-immune system interactions. Possible tools that target gut microbiome in MS, such the use of probiotics, postbiotics and prebiotics were analyzed too. Finally, we discussed the open question and the perspective of these microbiome-target therapies for people with MS and future research.